Divergent Developmental Pathways Among Staminate and Pistillate Flowers of Some Unusual Croton (Euphorbiaceae) - Thaowetsuwan, Pakkapol; Ritchie, Stuart; Riina, Ricarda; Ronse De Craene, Louis (Frontiers in Ecology and Evolution, 2020)
Croton is a mega-diverse genus of more than 1,200 species with great morphological diversity and highly dimorphic flowers. Staminate flowers generally possess petals and a variable number of stamens and lack of an ovary. Pistillate flowers generally lack petals or have filamentous structures instead; stamens are lacking, and the ovary is generally tricarpellate with divided styles. However, well-developed petals can be found in pistillate flowers of some African species and two New World sections, i.e., sect. Alabamenses and sect. Eluteria subsect. Eluteria. Our objectives are to compare ontogeny in dimorphic flowers of Croton which may elucidate the origin of petals, homology of the filamentous structures, nectaries, and diversity of androecium. The development of staminate and pistillate flowers of C. alabamensis (sect. Alabamenses) and C. schiedeanus (sect. Eluteria) was studied under the scanning electron microscope (SEM) and compared with C. chilensis (sect. Adenophylli) which has filamentous structures in pistillate flowers. In staminate flowers, petals develop in alternation with sepals and later the outermost stamen whorl develops opposite to the petals. In a much later stage, nectar glands emerge in alternation with the petals. In pistillate flowers, filamentous structures and petals share the same early development in alternation with the sepals. However, growth of the filamentous structures of C. chilensis becomes arrested, while petals of C. alabamensis and C. schiedeanus develop similar to those of the staminate flowers. The main conclusions of the study are: (1) Petals and filamentous structures are homologous based on their location and shape in early development. (2) Nectaries with variable morphology develop in antesepalous position and probably represent receptacular outgrowths and are not staminode. (3) Staminate flower development displays an unexpected diversity, including a floral cup in C. alabamensis. All investigated species have an unusual centrifugal initiation of the second stamen whorl. (4) The possible evolutionary loss and potential regain of petals among different species of Croton is discussed in relation to heterochrony. We suggest that the filamentous structures in pistillate flowers represent paedomorphic forms of petals of staminate flowers, and that the well-developed petals in C. alabamensis and C. schiedeanus are derived via a developmental reversion.